The effects of achievement goal orientations and safety climate on safe and unsafe behavior - Jung, JiHee; Park, YoungSeok (Korean Journal of Industrial and Organizational Psychology, 2014)
The purpose of this study is to test the effect of achievement goal orientations and safety climate on safe and unsafe behaviors. Safe behaviors were measured by observances and automatic safe behaviors, and unsafe behaviors by violations and mistakes. Three fifty employees from corporations were participated in this research. Both mastery approach goal and performance approach goal orientations have significant positive relations with the safe behaviors and negative relations with the unsafe behaviors, but both mastery avoidance goal and performance avoidance goal orientations have significant negative relations with the safe behaviors and positive relations with the unsafe behaviors. This results suggest to confirm the multiple goal perspective of the achievement goal orientation argued both mastery goal and performance goal orientations have relations with adaptive and maladaptive behaviors. Safety climates measured by five factors, management values, safety practice, safety training, safety communication, and supervisor leadership, were significant positive relations with safe behaviors and negative relations with unsafe behaviors. Specially safety climates have significantly stronger correlations with unintentional behaviors(automatic safe behavior and mistake) than intentional behaviors(observance and violation). The relative contributions of individual variables and organizational variables to safe and unsafe behaviors were discussed.